Economic expectations and private investment decision for the Peruvian consumer sector 2010Q4-2020Q1: Preliminary analysis under COVID-19 scenario - Miranda Peralta, Jorge Marcelo (2021)
This work estimates the relationship between the economic expectations given by Tobin's q variables, terms of exchange and 3-month economic expectations with private gross investment for the period from the first quarter of 2010 to the first quarter of 2020, under the stress scenario of the COVID-19 pandemic. Through an econometric model, results were obtained such as that the variation in private gross investment VIBP has an inertial behavior with a coefficient of 0.258791, shadow cost of capital or q of Tobin QTC with a coefficient of-0.03213, as well as terms of TI exchange with a coefficient of 0.805618. This indicates that the private investment decision by the companies analyzed depends on factors such as economic expectations, the inertial effect of investment and the shadow cost of capital expressed in Tobin's q. © 2021 by the authors;licensee Growing Science, Canada.